A confissão sacramental na Igreja Católica e o aconselhamento psicológico - Mercês, Gerson da Silva (2012)
The objective of this dissertation was to reflect on spiritual counseling and sacramental confession in the perspective of psychological counseling developed in the person-centered approach. To achieve this goal presented the history of confession since its inception, its historical evolution and its relationship with spiritual counseling. Secondly, presented the sacramental confession to the light of catholic theology, emphasizing the basic attitudes that the confessor should adopt. Then, I tried to understand the spiritual counseling and confession as aid relationship that approximate the relationship between counselor and client proposal by the personcentered approach for psychological counseling. In conclusion, I present the gains that the knowledge developed in the area of counseling can bring to the work of spiritual counselor and confessor